Long-term safety and efficacy of lumacaftor–ivacaftor therapy in children aged 6–11 years with cystic fibrosis homozygous for the F508del-CFTR mutation: a phase 3, open-label, extension study. Issue 7 (July 2021) - Chilvers, Mark A; Davies, Jane C; Milla, Carlos; Tian, Simon; Han, Zifei; Cornell, Alexandra G; Owen, Caroline A; Ratjen, Felix
Summary: Background: The safety and efficacy of 24 weeks of lumacaftor–ivacaftor combination therapy in children aged 6–11 years with cystic fibrosis homozygous for the F508del-CFTR mutation was previously shown in two phase 3 studies. Here, we report long-term safety and efficacy data. Methods: In this phase 3, open-label, multicentre, extension study (study 110), we examined the long-term safety, tolerability, and efficacy of lumacaftor–ivacaftor in children pooled from two phase 3 parent studies (open-label study 011B and randomised, placebo-controlled study 109). The study was conducted at 61 clinics in the USA, Australia, Belgium, Canada, Denmark, France, Germany, Sweden, and the UK. Children with cystic fibrosis homozygous for the F508del-CFTR mutation who had received lumacaftor–ivacaftor or placebo in the parent studies were treated with lumacaftor–ivacaftor for up to 96 weeks; those who had received the combination therapy in the parent studies (the treatment-to-treatment group) received up to 120 weeks of treatment in total. Participants aged 6–11 years at the start of the parent study received lumacaftor 200 mg–ivacaftor 250 mg orally once every 12 h; those aged 12 years or older received lumacaftor 400 mg–ivacaftor 250 mg orally once every 12 h. The primary endpoint was safety and tolerability in all children who had received at least one dose of the study drug. Secondary endpoints included change from baseline in lung clearance index 2·5% (LCI2·5 ), sweat chloride concentration, body-mass index, and Cystic Fibrosis Questionnaire–Revised respiratory domain score. This extension study is registered with ClinicalTrials.gov, NCT02544451, and has been completed. Findings: The extension study ran from Aug 13, 2015, to Aug 17, 2018. Of 239 children who enrolled in the study and received at least one dose of lumacaftor–ivacaftor, 215 (90%) completed 96 weeks of treatment. Most children (236 [99%] of 239 children) had adverse events that were mild (49 [21%] of 239) or moderate (148 [62%] of 239) in severity, and there was a low rate of adverse events leading to treatment discontinuation. The most frequently reported adverse events were common manifestations or complications of cystic fibrosis, such as cough and pulmonary exacerbation, or were consistent with the known safety profile of lumacaftor–ivacaftor in older children and adults. No new safety concerns were identified with extended lumacaftor–ivacaftor treatment. Children in the placebo-to-treatment group had improvements in efficacy endpoints consistent with those observed in the parent studies. Improvements observed in children treated with lumacaftor–ivacaftor in the parent study were generally maintained in the extension study. Interpretation: Lumacaftor–ivacaftor therapy in children homozygous for F508del-CFTR who initiated treatment at age 6–11 years was generally safe and well tolerated, and efficacy was sustained for up to 120 weeks. These data support the long-term use of lumacaftor–ivacaftor to treat children aged 6 years and older who are homozygous for the F508del-CFTR mutation. Funding: Vertex Pharmaceuticals Incorporated.